Full-scale comparison of UV/H2O2 and UV/Cl2 advanced oxidation: The degradation of micropollutant surrogates and the formation of disinfection byproducts. (15th September 2019) - Wang, Chengjin; Moore, Nathan; Bircher, Keith; Andrews, Susan; Hofmann, Ron
Abstract: The photolysis of chlorine by UV light leads to the formation of the hydroxyl radicals (OH) as well as reactive chlorine species (RCS) that can be effective as advanced oxidation processes (AOPs) for water treatment. Much of the research to date has been done at laboratory- or bench-scale. This study reports results from a model that demonstrates that the relative effectiveness of the UV/Cl2 AOP compared to the more traditional UV/H2 O2 AOP is a function of optical path length. As such, the relative effectiveness of the two treatment options evaluated at small scale may not reflect the relative performance at full-scale, making results previously obtained at small-scale potentially less scalable. This study therefore compares the performance of UV/Cl2 to UV/H2 O2 at a full-scale water treatment plant, using sucralose and caffeine as spiked surrogates for contaminants that are reactive solely to OH radicals, and to both OH and RCS, respectively. pH was varied between 6.5 and 8.0. The results demonstrated that when using a medium pressure UV lamp, UV/Cl2 might lead to approximately twice the production of OH radicals as UV/H2 O2 at pH 6.5 when using the same molar oxidant concentration, but adding chlorine to the UV reactor at pH 8.0 had a negligible impact on OH radical concentration in comparison to UV alone. The study also confirmed previous small-scale results that RCS can be a major contributor to UV/Cl2 treatment for compounds such as caffeine that are susceptible to RCS, with UV/Cl2 effective at both pH 6.5 and 8.0 for such compounds. Disinfection byproducts were monitored, with adsorbable organohalide (AOX) formation increasing by approximately 10 μg-Cl/L due to chlorine photolysis, but only at pH 6.5 and not at pH 8.0. This implies that UV/Cl2 might increase AOX mostly due to reaction between OH and organic precursors to make them more reactive with chlorine, and not due to RCS. The formation of specific DBPs of current or emerging regulatory interest was minimal under all conditions, except for chlorate. Chlorate yields were in the order of 6–18% of the photolysed chlorine. Graphical abstract: Image 1 Highlights: The relative effectiveness of MP UV/H2 O2 versus UV/Cl2 is light path length dependent. UV/Cl2 produced twice as much OH radical as UV/H2 O2 at pH 6.5. The reactive chlorine species generated in UV/Cl2 at pH 8.0 did not contribute to AOX formation. Chlorate yields were in the order of 6–18% of the photolysed chlorine in UV/Cl2 .